N-terminal Pro-B-Type Natriuretic Peptide and Malnutrition in Patients on Hemodialysis. (5th March 2020) - Ducros, Jacques; Larifla, Laurent; Merault, Henri; Galantine, Valérie; Bassien-Capsa, Valérie; Foucan, Lydia
Abstract : Natriuretic peptides, brain natriuretic peptide (BNP), and N-terminal probrain natriuretic peptide (NT-proBNP) are mainly known as diagnostic markers for heart failure with high diagnostic and prognostic values in the general population. In patients who are undergoing hemodialysis (HD), changes in NT-proBNP can be related to noncardiac problems such as fluid overload, inflammation, or malnutrition and can also be influenced by the dialysis characteristics. The current review aimed to summarize findings from studies on the association between NT-proBNP and malnutrition in HD patients. Articles published after 2009 and over a ten-year period were considered for inclusion. We first briefly discuss the traditional functions of NT-proBNP, and after, we describe the functions of this prohormone by focusing on its relation with protein energy wasting (PEW) in HD patients. Mechanisms that could explain these relationships were also discussed. Overall, 7 studies in which the investigation of the relations between NT-proBNP and nutritional status in HD patients were among the main objects were taken into account. NT-proBNP levels correlated with several factors described in the 4 categories of markers indicative of PEW (body mass and composition, muscle mass, biochemical criteria, and dietary intakes) and/or were associated with PEW. Interactions between several parameters could be involved in the association between NT-proBNP and malnutrition with a strong role of weight status. NT-proBNP is elevated in HD patients and is associated with malnutrition. Nevertheless, the prognostic value of NT-proBNP on nutritional status should be evaluated.